AWARENESS AND LIMITATIONS OF MEASURING VASCULAR AGEING IN EVERYDAY PRACTICE. A PILOT QUALITATIVE ANALYSIS FROM VASCAGENET(CA18216). (June 2022) - Triantafyllou, Areti; Elia, Stavria-Artemis; Park, Chloe; Climie, Rachel; Mayer, Christopher C.; Weber, Thomas; Panayiotou, Andrie G.
Abstract : Objective: Despite current evidence demonstrating the important role of Vascular ageing (VA) in cardiovascular risk assessment, its awareness and mostly implementation in everyday practice still lags significantly. To effectively assess the need for future target strategies for health providers, a qualitative questionnaire was developed. The aim of this analysis was to identify perceptions and factors associated with omitting VA assessment in a group of clinicians and researchers. Design and method: An online qualitative questionnaire based on intentionally left open-ended key questions identified by a Network for Research in Vascular Ageing (VascAgeNet) COST Action(CA18216) expert working group was developed and distributed to participants working in the field of VA, in order to globally assess knowledge and perceptions. Importance of VA was evaluated on a scale 0(least important)-5(very important). Results: Out of the 127 responses, 104 questionnaires were complete. The mean age of participants was 42.5 ± 10.5 years, 60.6% male. 43.3% were clinicians (mostly cardiologists, internists, and endocrinologists) and 56.7% were other scientists (mostly computer scientists and physiologists). Although participants were aware of the role of VA and scored median 5/5 (very important) on the evaluation scale, only 53.8% measured it in the research setting and only 16.3% in everyday clinical practice. Amongst the most frequently identified limiting factors regarding clinical setting were time(31.5%), lack of reimbursement of tests(22.3%), cost of equipment(16.7%), guidelines(13%), validation data(5.6%) and devices(9.4%). 15.6% considered that there was no clinical benefit. Participants who measured VA in clinical practice considered VA significantly more important than those who didn't measure it (0% vs.3.3%(1–2), 17.6% vs.39.3%(3–4), 82.4% vs.57.4%(5), respectively, p = 0.029). Similar were the results in research setting (1.8% vs.4.5%(1–2), 28.6% vs. 50.0%(3–4), 69.6% vs. 45.5%(5), respectively, p = 0.053). Table 1 presents the main results, according to the participants' status. Conclusions: Although aware of the importance of VA in cardiovascular risk assessment, participants are still unable to implement it in their clinical practice. Our results identify for the first time some important factors, which informed the construction of a quantitative questionnaire for confirmation in larger populations, and could constitute a small startup for future experts' recommendations.